Chapter Супралексический префикс по- в русском и болгарском языках - Slavkova, Svetlana (Biblioteca di Studi Slavistici, 2017)
The aim of this paper is to compare the superlexical prefixes of Russian and Bulgarian. The main focus is on delimitative and attenuative po- in derived PF forms as well as in secondary IPF verbs. Using the Russian-Bulgarian parallel corpus, I show that there is a functional parallelism between PF and IPF delimitatives in Russian and Bulgarian. The semantic similarity between delimitative and attenuative meaning is the basis for expressing special pragmatic functions by means of both PF and IPF poattenuatives in Bulgarian, while attenuative po-verbs in Russian express specific pragmatic meanings primarily via PF forms.